(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
The experiment was carried out during three consecutive years (2023–24, 2024–25 and 2025–26) on Apple ber. Among the various foliar pathogens affecting ber, the black spot caused by a fungus Isariopsis personata var. zizyphi producing regular black coloured fringed spots on the lower leaf surface. Spraying of Tebuconazole 50% + Trifloxystrobin 25% (WG) (0.1%) immediately after the appearance of the symptoms found most effective by reducing the leaf spot disease from 46.94 PDI to 17.20 PDI with yield of 64.39 kg/ tree.